Normothermic ex situ pancreas perfusion for the preservation of porcine pancreas grafts. Issue 5 (31st March 2022) - Mazilescu, Laura I.; Parmentier, Catherine; Kalimuthu, Sangeetha N.; Ganesh, Sujani; Kawamura, Masataka; Goto, Toru; Noguchi, Yuki; Selzner, Markus; Reichman, Trevor W.
Abstract: Pancreas transplantation improves and extends the life of patients with insulin‐dependent diabetes. Pancreata from extended criteria donors have been increasingly used due to the scarcity of available grafts. Normothermic ex situ pancreas perfusion (NESPP) can keep grafts metabolically active, potentially allowing for assessment and organ repair, and could improve outcomes of marginal grafts. A novel NESPP technique was developed and tested. Porcine pancreata were removed after a short period of warm ischemia and subjected to 6 h of NESPP. Perfusion parameters, potential graft assessment markers and graft injury were measured. Next, pancreata subjected to 3 h of NESPP were transplanted and animals were followed for up to 3 days. Graft function and injury post‐transplantation were evaluated. Using this novel system of perfusion, pancreata were perfused for an extended period of time with minimal edema. Histology at the end of perfusion showed intact islet cells with only mild signs of tissue injury. NESPP transplanted grafts showed immediate function after transplantation, with glucose levels in normal range. NESPP maintains a physiologic environment and excellent graft function without causing significant graft injury. Porcine pancreas transplantation is feasible and allows for in vivo graft assessment of pancreas function and injury after NESPP. Abstract : Normothermic ex situ pancreas perfusion maintains a physiologic environment and excellent graft function and represents a platform for graft preservation and assessment.